Sustainable Supply Chain Finance and Corporate Performance: Moderating Role of Regulatory Policies - Wang, Qiaoran (Simen Owen Academic Proceedings Series, 2025)
Sustainable Supply Chain Finance (SSCF) has emerged as a pivotal mechanism for integrating financial management with sustainability objectives amid increasingly complex global supply networks. As regulatory scrutiny intensifies worldwide, SSCF is transforming traditional financing models by embedding environmental, social, and governance (ESG) criteria into financial decision-making structures. Despite growing corporate adoption, scholarly inquiry has yet to sufficiently examine how regulatory frameworks influence the relationship between SSCF implementation and corporate performance. Addressing this research gap, the present study explores how differences in regulatory environments moderate SSCF’s performance outcomes. Employing a comparative case study design, the research investigates Siemens (Germany), Huawei (China), and Unilever (Netherlands), each operating under distinct regulatory conditions. The results indicate that SSCF adoption consistently enhances both operational efficiency and sustainability performance, with the positive effects being more pronounced in rule-based regulatory contexts. The study contributes to the literature by integrating insights from financial innovation theory with institutional and regulatory economics, proposing a moderated mediation framework that elucidates how policy environments amplify or constrain SSCF’s advantages. These findings hold practical significance for firms seeking to optimize SSCF strategies and for policymakers aiming to construct regulatory systems that foster sustainable financial practices across global supply chains.